Le Madri in trono di Fondo Patturelli a Capua. Rapporti tra i piccoli fittili votivi, la coroplastica maggiore e le statue in tufo. Alcune considerazioni (ACME, 2020)
The iconography of the seated woman with a baby is surely the most significant in the terracotta votive offerings from the Fondo Patturelli sanctuary at Capua. This subject is also testified by the well-known tufa statues and by some samples in the major terracotta votives. This contribution aims to provide some preliminary remarks, starting from the small votives in comparison to the other two object categories, focusing on stylistic and formal features and considering the similarities and the differences, in order to trace further possible hypothesis on the nature and reason of each votive offering.